Whole-body hypothermia in mild neonatal encephalopathy: protocol for a multicentre phase III randomised controlled trial - Garegrat, R; Montaldo, P; Burgod, C; Pant, S; Mazlan, M; Palanisami, B; Chakkarapani, E; Woolfall, K; Johnson, S; Grant, PE; Land, S; Mahmoud, M; et al. (BioMed Central, 2024)
Background: Mild hypoxic ischemic encephalopathy is associated with sub optimal cognition and learning difficulties at school age. Although whole-body hypothermia reduces death and disability after moderate or severe encephalopathy in high-income countries, the safety and efficacy of hypothermia in mild encephalopathy is not known. The cooling in mild encephalopathy (COMET) trial will examine if whole-body hypothermia improves cognitive development of neonates with mild encephalopathy. Methods: The COMET trial is a phase III multicentre open label two-arm randomised controlled trial with masked outcome assessments. A total of 426 neonates with mild encephalopathy will be recruited from 50 to 60 NHS hospitals over 2 ½ years following parental consent. The neonates will be randomised to 72 h of whole-body hypothermia (33.5 ± 0.5 C) or normothermia (37.0 ± 0.5 C) within six hours or age. Prior to the recruitment front line clinical staff will be trained and certified on expanded modified Sarnat staging for encephalopathy. The neurological assessment of all screened and recruited cases will be video recorded and centrally assessed for quality assurance. If recruitment occurs at a non-cooling centre, neonates in both arms will be transferred to a cooling centre for continued care, after randomisation. All neonates will have continuous amplitude integrated electroencephalography (aEEG) at least for the first 48 h to monitor for seizures. Predefined safety outcomes will be documented, and data collected to assess resource utilization of health care. A central team masked to trial group allocation will assess neurodevelopmental outcomes at 2 years of age. The primary outcome is mean difference in composite cognitive scores on Bayley scales of Infant and Toddler development 4th Edition. Discussion: The COMET trial will establish the safety and efficacy of whole-body hypothermia for mild hypoxic ischaemic encephalopathy and inform national and international guidelines in high income countries. It will also provide an economic assessment of whole-body hypothermia therapy for mild encephalopathy in the NHS on cost-effectiveness grounds. Trial registration number: NCT05889507 June 5, 2023.